2008
DOI: 10.1080/08897070802093312
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Problem: Methamphetamine Abuse among Treatment Seeking Youth

Abstract: This study examined correlates of methamphetamine (MA) and marijuana (MJ) use and treatment response among treatment-involved youth (N = 4,430) in Los Angeles County, California treated between 2000 and 2005. Of the sample, 912 (21%) were primary MA and 3,518 (79%) were primary MJ users. Correlates of increased MA use included being female, White, Asian or Latino, older age, previous treatment involvement, legal status of probation or parole, and initiating drug use at an older age. Treatment trends showed a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…For example, adolescent girls are more likely to use methamphetamine than boys (Gonzales, Ang, McCann, & Rawson, 2008;Rawson, Gonzales, McCann, & Obert, 2005), and, according to a recent report published by the ONDCP, more than 12% of adolescent girls living in Nevada reported a history of methamphetamine use (ONDCP, 2008). In fact, the weight loss side effects of stimulants like methamphetamine are so strong that they are sometimes used to treat severe exogenous obesity in forms like Desoxyn (methamphetamine hydrochloride; see Food and Drug Administration [FDA], 2007).…”
Section: Western Culture Weight-loss and Drug Use In Womenmentioning
confidence: 92%
“…For example, adolescent girls are more likely to use methamphetamine than boys (Gonzales, Ang, McCann, & Rawson, 2008;Rawson, Gonzales, McCann, & Obert, 2005), and, according to a recent report published by the ONDCP, more than 12% of adolescent girls living in Nevada reported a history of methamphetamine use (ONDCP, 2008). In fact, the weight loss side effects of stimulants like methamphetamine are so strong that they are sometimes used to treat severe exogenous obesity in forms like Desoxyn (methamphetamine hydrochloride; see Food and Drug Administration [FDA], 2007).…”
Section: Western Culture Weight-loss and Drug Use In Womenmentioning
confidence: 92%
“…While rates of adolescent MA use are relatively low compared to other drugs of abuse, studies suggest the rates of adolescents seeking treatment for MA abuse increased in the early 2000s [4, 5]. The behavioral, cognitive, and neurobiological effects of MA may differ in adolescents compared to adults, as adolescence is a dynamic period of brain and behavioral maturation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some adolescents begin using drugs during this time and it has been reported that adolescent-onset users transition to dependence more readily than adults (Chen et al 2009) and have poorer treatment outcomes (Gonzales et al 2008;Chen et al 2009). …”
Section: Introductionmentioning
confidence: 99%